Conceptual Design of a Small Helicopter - Azli, Ahmad Razin; Yaakub, Mohd Fauzi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The purpose of the study is to propose a conceptual design process by developing the aircraft from the scratch and to optimize the design using a structured approach. As part of this study, a concept for a small helicopter was developed. From this study, the main parameters to be had for conceptual phases is the maximum take-off weight, maximum rotor diameter, engine to be used, major drawing for proposed design, and centre of gravity envelope. Due to assumed simplicity of the rotor design and taking into account some technological constraints, the main approach for the conceptual design is by dedicating design which would influence satisfactory improvement in a performance of a small helicopter from parametric study and pre-existing specifications. The results obtain from this study will be the benchmark and within the constraints of further improvement. From this study, preliminary stages of development for small helicopter are critical in reviewing and modifying the future aircrafts.